2016
DOI: 10.3390/ma9090748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Oxygen and Immersion Time on the Corrosion Behaviour of Mild Steel in Bicarbonate/Chloride Solution

Abstract: Abstract:The electrochemical behavior of mild steel in bicarbonate solution at different dissolved oxygen (DO) concentrations and immersion times has been studied under dynamic conditions using electrochemical techniques. The results show that both DO and immersion times influence the morphology of the corrosion products. In comparative tests, the corrosion rate was systematically found to be lower in solutions with lower DO, lower HCO 3 − concentrations and longer immersion time. The SEM analyses reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This contradicts the findings of determining the instantaneous corrosion rate of C1018 carbon steel in CO 2 -saturated solutions by the electrochemical impedance spectroscopy and linear polarization resistance that the corrosion rate of C1018 carbon steel decreases with increasing of the NaCl concentration [15]. A decrease in the corrosion rate of low-carbon steel immersed in the NaCl solution could be due to a decrease in the DO and HCO 3 concentrations or an increase in the immersion time [45].…”
Section: Corrosion Ratementioning
confidence: 67%
See 2 more Smart Citations
“…This contradicts the findings of determining the instantaneous corrosion rate of C1018 carbon steel in CO 2 -saturated solutions by the electrochemical impedance spectroscopy and linear polarization resistance that the corrosion rate of C1018 carbon steel decreases with increasing of the NaCl concentration [15]. A decrease in the corrosion rate of low-carbon steel immersed in the NaCl solution could be due to a decrease in the DO and HCO 3 concentrations or an increase in the immersion time [45].…”
Section: Corrosion Ratementioning
confidence: 67%
“…(5) permits us to predict the change of low-carbon steel in an aqueous environment and may simulate any environmental condition to which a weight change level of the mild steel structure may occur in the saline water at any time. It has been reported that the immersion time and the level of dissolved oxygen (DO) in aqueous solution can influence the morphology and composition of the corrosion products formed on the low-carbon steel in NaCl solution [ 45 ]. Effect of Cl − ions on the weight change of low-carbon steel can be interpreted by the characterization of the metal complexes formed between Fe contained in mild steel and the Cl − ions [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, following the first phase, their corrosion rates decrease until about 21 days of exposure. The decrease in corrosion rate can be related to the formation of passive film on the surface of carbon steel which behaves a protective layer from a further corrosion process (Gaius Debi Eyu et al, 2016). However, the corrosion rates increase slightly up to the 30 days of exposure in both reference solutions, but not in the solutions from Karangsong and Eretan sites.…”
Section: The Measurement Of Seawater Parameters and The Observation Omentioning
confidence: 99%
“…Localised corrosion, like pitting corrosion, is the main cause of failure of carbon steel pipelines (Moore, 2012). Pitting corrosion of mild steel in bicarbonate (HCO 3 -) -chloride solution has been reported in our previous work (Eyu, Will, Dekkers, & MacLeod, 2016) and is relevant to the oil and gas industry, where wells are exposed to significant concentrations of bicarbonate and chloride ions.…”
Section: 1mentioning
confidence: 99%